Temperature-sensitive mutations for live-attenuated Rift Valley fever vaccines: implications from other RNA viruses - Nishiyama, Shoko; Ikegami, Tetsuro (Frontiers in Microbiology, 2015)
Rift Valley fever (RVF) is a mosquito-borne zoonotic disease endemic to the African continent. RVF is characterized by high rate of abortions in ruminants and hemorrhagic fever, encephalitis, or blindness in humans. RVF is caused by the Rift Valley fever virus (RVFV: genus Phlebovirus, family Bunyaviridae). Vaccination is the only known effective strategy to prevent the disease, but there are no licensed RVF vaccines available for humans. A live-attenuated vaccine candidate derived from the wild-type pathogenic Egyptian ZH548 strain, MP-12, has been conditionally licensed for veterinary use in the U.S. MP-12 displays a temperature-sensitive (ts) phenotype and does not replicate at 41°C. The ts mutation limits viral replication at a specific body temperature and may lead to an attenuation of the virus. Here we will review well-characterized ts mutations for RNA viruses, and further discuss the potential in designing novel live-attenuated vaccines for RVF.